Large lipid-rich coronary plaques detected by near-infrared spectroscopy at non-stented sites in the target artery identify patients likely to experience future major adverse cardiovascular events. (22nd January 2016) - Madder, Ryan D.; Husaini, Mustafa; Davis, Alan T.; VanOosterhout, Stacie; Khan, Mohsin; Wohns, David; McNamara, Richard F.; Wolschleger, Kevin; Gribar, John; Collins, J. Stewart; Jacoby, Mark; Decker, Jeffrey M.; et al.
Abstract: Aims: A recent study demonstrated that intracoronary near-infrared spectroscopy (NIRS) findings in non-target vessels are associated with major adverse cardiovascular and cerebrovascular events (MACCE). It is unknown whether NIRS findings at non-stented sites in target vessels are similarly associated with future MACCE. This study evaluated the association between large lipid-rich plaques (LRP) detected by NIRS at non-stented sites in a target artery and subsequent MACCE. Methods and results: This study evaluated 121 consecutive registry patients undergoing NIRS imaging in a target artery. After excluding stented segments, target arteries were evaluated for a large LRP, defined as a maximum lipid core burden index in 4 mm (maxLCBI4 mm ) ≥400. Excluding events in stented segments, Cox regression analysis was performed to evaluate for an association between a maxLCBI4 mm ≥400 and future MACCE, defined as all-cause mortality, non-fatal acute coronary syndrome, and cerebrovascular events. NIRS detected a maxLCBI4 mm ≥400 in a non-stented segment of the target artery in 17.4% of patients. The only baseline clinical variable marginally associated with MACCE was ejection fraction (HR 0.96, 95% CI 0.93–1.00, P = 0.054). A maxLCBI4 mm ≥400 in a non-stented segment at baseline was significantly associated with MACCE during follow-up (HR 10.2, 95% CI 3.4–30.6, P < 0.001). Conclusion: Detection of large LRP by NIRS at non-stented sites in a target artery was associated with an increased risk of future MACCE. These findings support ongoing prospective studies to further evaluate the ability of NIRS to identify vulnerable patients.